Faktor Penghambat Penanganan Pelanggaran Praktik Politik Uang Oleh Sentra Gakkumdu Kabupaten Gorontalo Pada Pemilihan Umum Tahun 2019 - Putri Ramadhanti Anton Taha; Moh. Rusdiyanto U. Puluhulawa; Nuvazria Achir (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This study aims to examine and analyze the inhibiting factors in the handling of violations of money politics practices by the Gorontalo Regency Gakkumdu Center in the 2019 general election. The research method used in this study is the empirical legal research method, which is research with field data as the main source of data, such as the results of observations and interviews. The results of this study show that in handling the practice of money politics by the Gakkumdu center of Gorontalo Regency in the 2019 general election it has gone well in accordance with the established regulations, but in terms of law enforcement given it is still not firm and relatively light it cannot make the perpetrators deterrent to their actions. And there are factors that hinder the handling process, namely the lack of time given in carrying out a case handling process. This factor makes the members of the Gorontalo Regency Gakkumdu Center not optimal in completing the handling of money politics practices that occurred during the 2019 general election.